Accessing Targeted Therapies: A Potential Roadblock to Implementing Precision Oncology?. Issue 7 (July 2021) - von Itzstein, Mitchell S.; Smith, Mary L.; Railey, Elda; White, Carol B.; Dieterich, Julianne S.; Garrett-Mayer, Liz; Bruinooge, Suanna S.; Freedman, Andrew N.; De Moor, Janet; Gray, Stacy W.; Park, Jason Y.; Yan, Jingsheng; et al.
Abstract : PURPOSE: Advances in genomic techniques have led to increased use of next-generation sequencing (NGS). We evaluated the extent to which these tests guide treatment decisions. METHODS: We developed and distributed a survey assessing NGS use and outcomes to a survey pool of ASCO members. Comparisons between groups were performed with Wilcoxon two-sample, chi-square, and Fisher's exact tests. RESULTS: Among 178 respondents, 62% were male, 54% White, and 67% affiliated with academic centers. More than half (56%) indicated that NGS provided actionable information to a moderate or great extent. Use was highest (median ≥ 70% of cases) for lung and gastric cancer, and lowest (median < 25% of cases) in head and neck and genitourinary cancers. Approximately one third of respondents reported that, despite identification of an actionable molecular variant, patients were sometimes or often unable to access the relevant US Food and Drug Administration–approved therapy. When NGS did not provide actionable results, individuals reporting great or moderate guidance overall from NGS in treatment recommendations were more likely to request the compassionate use of an unapproved drug ( P < .001), enroll on a clinical trial ( P < .01), or treat off-label with a drug approved for another indication ( P = .02). CONCLUSION: When NGS identifies an actionable result, a substantial proportion of clinicians reported encountering challenges obtaining approved therapies on the basis of these results. Perceived overall impact of NGS appears associated with clinical behavior unrelated to actionable NGS test results, including pursuing off-label or compassionate use of unapproved therapies or referring to a clinical trial.